Wideband mid-infrared thermal emitter based on stacked nanocavity metasurfaces. (9th December 2021) - Cao, Tun; Lian, Meng; Liu, Kuan; Lou, Xianchao; Guo, Yaoming; Guo, Dongming
Abstract: Efficient thermal radiation in the mid-infrared (M-IR) region is of supreme importance for many applications including thermal imaging and sensing, thermal infrared light sources, infrared spectroscopy, emissivity coatings, and camouflage. The ability to control light makes metasurfaces an attractive platform for infrared applications. Recently, different metamaterials have been proposed to achieve high thermal radiation. To date, broadening the radiation bandwidth of a metasurface emitter (meta-emitter) has become a key goal to enable extensive applications. We experimentally demonstrate a broadband M-IR thermal emitter using stacked nanocavity metasurface consisting of two pairs of circular-shaped dielectric (Si3 N4 )–metal (Au) stacks. A high thermal radiation can be obtained by engineering the geometry of nanocavity metasurfaces. Such a meta-emitter provides wideband and broad angular absorptance of both p- and s-polarized light, offering a wideband thermal radiation with an average emissivity of more than 80% in the M-IR atmospheric window of 8–14 μ m. The experimental illustration together with the theoretical framework establishes a basis for designing broadband thermal emitters, which, as anticipated, will initiate a promising avenue to M-IR sources.